Diagnosis, comorbidities, and management of restless legs syndrome. (August 2014) - Becker, Philip M.; Novak, Marta
Abstract Objective: This narrative review describes the differential diagnosis of restless legs syndrome, and provides an overview of the evidence for the associations between RLS and potential comorbidities. Secondary causes of RLS and the characteristics of pediatric RLS are also discussed. Finally, management strategies for RLS are summarized. Methods: The review began with a comprehensive PubMed search for 'restless legs syndrome/Willis-Ekbom disease' in combination with the following: anxiety, arthritis, attention-deficit hyperactivity disorder, cardiac, cardiovascular disease, comorbidities, depression, end-stage renal disease, erectile dysfunction, fibromyalgia, insomnia, kidney disease, liver disease, migraine, mood disorder, multiple sclerosis, narcolepsy, neuropathy, obesity, pain, Parkinson's disease, polyneuropathy, pregnancy, psychiatric disorder, sleep disorder, somatoform pain disorder, and uremia. Additional papers were identified by reviewing the reference lists of retrieved publications. Results and Conclusions: Although clinical diagnosis of RLS can be straightforward, diagnostic challenges may arise when patients present with comorbid conditions. Comorbidities of RLS include insomnia, depressive and anxiety disorders, and pain disorders. Differential diagnosis is particularly important, as some of the medications used to treat insomnia and depression may exacerbate RLS symptoms. Appropriate diagnosis and management of RLS symptoms may benefit patient well-being and, in some cases, may lessen comorbid disease burden. Therefore, it is important that physicians are aware of the presence of RLS when treating patients with conditions that commonly co-occur with the disorder.